Modeling Gravity Segregation In Stratified And Dipping Reservoir Of Volatile Oil - Ego Syahrial (Scientific Contributions Oil and Gas, 2010)
In this paper, we investigate gravity segregation in stratified and dipping reservoir of volatile oil under gas injection. A new efficient compositional simulation approach was used in this study to investigate the influence of gravity segregation and their magnitude in the case of gas injection into a volatile oil reservoir. The results show that in stratified and dipping reservoirs where the permeability decreases with depth, smaller the vertical to horizontal permeability ratio, lesser is the effect of gravity segregation, better is the sweep efficiency and hence better is the recovery. In the case of increasing permeability with depth in stratified dipping reservoirs, an up-dip gas injection into a volatile oil reservoir was found to be a favourable condition in term of recovery. Gravity forces have a considerable effect on volatile oil recovery via gas injection and the need for determining not only the fluid characteristics but also the reservoir heterogeneities was significant